Iron ditch casting material and preparation method thereof

By using iron groove castables mainly composed of fused silica, silicon carbide and carbon, combined with silicon sol and other additives, the existing castables for iron grooves have high volume density, high thermal expansion coefficient and low thermal fold strength, and a lower unit amount of material, higher anti-iron erosion performance and longer service life are achieved.

CN119306483BActive Publication Date: 2025-04-08BEIJING ALLIED RONGDA ENG MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411846642.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-04-08
Estimated Expiration
2044-12-16

AI Technical Summary

Technical Problem

The existing Al2O3-SiC-C iron groove castable for iron ditches has problems such as high volume density, high thermal expansion coefficient and low thermal folding strength, resulting in large unit material consumption, high material consumption cost, poor thermal shock stability and poor anti-iron erosion performance.

Method used

Iron groove castable mainly composed of fused quartz, silicon carbide and carbon is used, silicon sol is used as a binding agent, and additives such as zirconium silicon powder, quartz powder, metal silicon powder, iron scale powder, hydrated calcium silicate, water reducing agent and explosion-proof fiber are added to reduce the bulk density and thermal expansion coefficient and improve the thermal folding strength.

Benefits of technology

It reduces the cost of refractory materials per unit of iron ditch, reduces cracks, improves the anti-iron erosion performance, extends the service life, and improves the thermal shock stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention relates to the technical field of refractory materials, and specifically to an iron ditch castable and a preparation method thereof. The iron ditch castable includes fused quartz, silicon carbide, quartz powder, zirconium-containing silicon powder, spherical asphalt, wettable flake graphite, metallic silicon powder, iron scale powder, hydrated calcium silicate, water reducer, explosion-proof fiber and silica sol. The raw materials of the iron ditch castable of the present invention can cooperate with each other to reduce the volume density and thermal expansion coefficient of the iron ditch castable, and improve the thermal bending strength, thereby reducing the unit refractory material consumption cost of the iron ditch, reducing cracking, and improving the resistance to molten iron scouring. It is more in line with the characteristics of the iron ditch and has a longer service life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of refractory materials, and in particular to an iron ditch castable and a preparation method thereof. Background Art

[0002] The iron ditch is located at the rear end of the slag skimmer of the main iron ditch of the blast furnace. When the blast furnace is tapping iron, the high-temperature molten iron and slag are diverted to the slag ditch at the upper slag of the slag skimmer, and the lower molten iron flows into the iron ditch through the bottom channel of the slag skimmer, and then flows into the iron lad or torpedo lad through the iron ditch, and then transferred to steelmaking. The iron ditch must withstand the scouring of high-temperature molten iron of about 1450℃ when the blast furnace is tapping iron. After the blast furnace is blocked, it is exposed to air at near normal temperature. Therefore, the iron ditch castable must not only resist the scouring of high-temperature molten iron, but also resist frequent thermal shock.

[0003] At present, the most common castables for iron ditch are Al2O3-SiC-C, the main raw materials are high-grade bauxite, mullite, corundum, silicon carbide and carbon, the binder is mostly pure calcium aluminate cement, and a small amount is sol-bonded, and explosion-proof fiber and metal aluminum powder are added as explosion-proof agents. At present, almost all castables for iron ditch are made of Al2O3-SiC-C, but some new additives or admixtures or emerging binders are introduced on the basis of this main material for improvement and optimization. There has never been any report on SiO2-SiC-C lightweight castables for iron ditch.

[0004] The current iron ditch uses Al2O3-SiC-C iron ditch castables, which are mostly made of high-grade alumina composite with a certain amount of corundum, with high volume density, generally 2.5-2.7g / cm 3 The main raw material of large blast furnace iron channel castable is fused corundum, and its bulk density is generally greater than 2.7g / cm 3 The high volume density leads to a large amount of material per unit of the iron ditch, and the weight of refractory consumption increases accordingly, which means an increase in the unit refractory consumption cost of the iron ditch.

[0005] The current iron ditch uses Al2O3-SiC-C iron ditch castable, which still has the problem of high thermal expansion coefficient, which is generally (5-6)×10 -6 / ℃, the higher the thermal expansion coefficient of the material, the lower the thermal shock stability; the groove lining is prone to cracks under the impact of hot and cold fluctuations, and the higher the thermal expansion coefficient, the more serious the cracks will be.

[0006] The current iron ditch uses Al2O3-SiC-C iron ditch castables, and the hot flexural strength at 1400℃ is generally 3-5MPa, and the hot flexural strength at 1450℃ is mostly lower than 3MPa. The low hot flexural strength restricts the improvement of the iron ditch castable's anti-molten iron erosion performance, which leads to a series of problems such as short maintenance life of the iron ditch, frequent maintenance, and high consumption of refractory materials per ton of iron. Summary of the invention

[0007] The invention provides an iron ditch castable and a preparation method and application thereof, which are used to solve the problems of high bulk density, high thermal expansion coefficient and low thermal flexural strength of the existing Al2O3-SiC-C iron ditch castable for iron water ditch.

[0008] According to a first aspect of the present invention, the present invention provides an iron ditch castable, comprising fused quartz, silicon carbide, quartz powder, zirconium-containing silicon powder, spherical asphalt, wettable flake graphite, metallic silicon powder, iron scale powder, hydrated calcium silicate, a water reducer, explosion-proof fiber and silica sol.

[0009] In view of the defects of the Al2O3-SiC-C iron ditch castable used in the above-mentioned iron ditch, the present invention provides an iron ditch castable, the main raw materials of which are fused quartz, silicon carbide and carbon, silica sol as a binder, and zirconium-containing silicon micropowder, quartz powder, metal silicon powder, iron scale powder (mineralizer), hydrated calcium silicate, water reducer and explosion-proof fiber and other additives, so that the raw materials can cooperate with each other, reduce the volume density and thermal expansion coefficient of the iron ditch castable, and improve the thermal folding strength, thereby reducing the unit refractory material consumption cost of the iron ditch, reducing cracking, and improving the anti-iron scouring performance, which is more in line with the characteristics of the iron ditch and has a longer service life. Among them, the thermal expansion coefficient of fused quartz ((0.5-0.6)×10 -6 / ℃) is almost the smallest among all refractory materials, and has a low bulk density of 2.0-2.21g / cm 3 The combination of the two characteristics can make it have excellent thermal shock stability. In addition, fused quartz is a molten refractory raw material with extremely low porosity. Most molten metals have poor wettability to it, so it has excellent resistance to molten metal erosion. The iron ditch castable of the present invention is combined with silica sol without introducing other low-melting impurities. The added silicon carbide and carbon are both non-oxides with high refractoriness. Therefore, it has similar properties to pure siliceous refractory materials, and the load softening temperature is close to the refractoriness. It has extremely high hot flexural strength in the range of molten iron temperature of about 1450°C, which gives the iron ditch castable of the present invention high resistance to molten iron scouring.

[0010] Furthermore, according to the weight percentage, it includes 40-70 parts of fused quartz, 9-18 parts of silicon carbide, 12-26 parts of quartz powder, 2-10 parts of zirconium-containing silicon powder, 1.5-3 parts of spherical asphalt, 1-3 parts of wettable flake graphite, 1.5-3 parts of metallic silicon powder, 0.2-0.5 parts of iron scale powder, 0.05-0.3 parts of hydrated calcium silicate, 0.10-0.25 parts of water reducer, 0.05-0.12 parts of explosion-proof fiber and 8.0-10.0 parts of silica sol. By limiting the amount of each raw material within a reasonable range, the raw materials can play a better synergistic role, better reduce the volume density and thermal expansion coefficient of the iron ditch castable, and improve the hot bending strength.

[0011] In some specific embodiments, the material includes, by weight, 55-62 parts of fused quartz, 14-18 parts of silicon carbide, 12-17 parts of quartz powder, 4.5-6.5 parts of zirconium-containing silicon powder, 1.5-2.5 parts of spherical asphalt, 1-1.5 parts of wettable flake graphite, 1.5-2 parts of metallic silicon powder, 0.2-0.5 parts of iron scale powder, 0.05-0.15 parts of hydrated calcium silicate, 0.14-0.18 parts of water reducer, 0.05-0.08 parts of explosion-proof fiber and 8.0-9.5 parts of silica sol.

[0012] Further, the fused quartz includes 15-25 parts of fused quartz with a particle size of 0-1mm, 15-25 parts of fused quartz with a particle size of 1-3mm, and 10-20 parts of fused quartz with a particle size of 3-5mm. By selecting fused quartz of different particle size ranges for combined use, it is more conducive to improving the thermal shock stability of the iron ditch castable. The combined use of fused quartz of different particle sizes can improve the physical properties of the castable, such as strength, density and porosity, which is very important for improving the overall performance of the castable. Suitable particle size distribution helps to improve the fluidity of the castable, ensure that the castable can evenly fill the mold, and reduce the generation of pores and cracks. Fine-grained fused quartz can better fill the gaps between other raw materials, improve the density of the castable, and thus improve its thermal stability and strength.

[0013] Furthermore, the content of SiO2 in the fused quartz is ≥99%. By limiting the content of SiO2 in the fused quartz, it is beneficial to maintain its chemical stability and improve the quality of the iron trough castable.

[0014] Further, the silicon carbide comprises 4-8 parts of silicon carbide with a particle size of 0-1 mm and 4-8 parts of silicon carbide with a particle size of 0.04-0.05 mm; and / or, the silicon carbide is 98 silicon carbide. By defining the characteristics of the performance of silicon carbide, the quality of the iron trough castable can be further improved.

[0015] Furthermore, the quartz powder includes 8-18 parts of fused quartz powder with a particle size of 0.07-0.08 mm and 8-18 parts of high-purity quartz powder with a particle size of 0.085-0.09 mm. By defining the characteristics of the performance of the quartz powder, the quality of the iron trough castable can be further improved.

[0016] Furthermore, the sum of the contents of SiO2 and ZrO2 in the zirconium-containing silicon micropowder is ≥95%, and the particle size is ≤1 um.

[0017] Furthermore, the particle size of the ball pitch is 0-0.5 mm; and / or the particle size of the wettable flake graphite is 0-0.5 mm; and / or the particle size of the iron scale powder is 0.04-0.05 mm; and / or the particle size of the hydrated calcium silicate is 0.07-0.08 mm. By limiting the particle sizes of the ball pitch, wettable flake graphite, iron scale powder and hydrated calcium silicate to a reasonable range, the overall performance of the iron ditch castable can be further improved.

[0018] Furthermore, the explosion-proof fiber is a hollow explosion-proof fiber. The hollow explosion-proof fiber has the characteristics of low density, high strength, heat insulation, thermal insulation, electrical insulation, etc., and can further improve the overall performance of the iron trough castable.

[0019] Furthermore, the iron trough castable satisfies at least one of the following characteristics (1)-(5):

[0020] (1) Bulk density is 1.85-2.1g / cm 3 ;

[0021] (2) Thermal expansion coefficient is 1.5-2.5×10 -6 / K;

[0022] (3) The compressive strength after treatment at 110℃ for 24h is 30-35MPa; the compressive strength after treatment at 1000℃ for 3h is 25-40MPa; the compressive strength after treatment at 1500℃ for 3h is 50-60MPa;

[0023] (4) The post-sintering line change rate after treatment at 1500℃ for 3h is +(0.1-0.15)%;

[0024] (5) The hot flexural strength after treatment at 1450℃ for 1h is 5-8MPa.

[0025] According to a second aspect of the present invention, the present invention also provides a method for preparing the above-mentioned iron ditch castable, comprising the following steps:

[0026] The mixed material is obtained by mixing fused quartz, silicon carbide, quartz powder, zirconium-containing silicon powder, spherical asphalt, wettable flake graphite, metallic silicon powder, iron scale powder, hydrated calcium silicate, water reducing agent and explosion-proof fiber; and the obtained mixed material is stirred evenly with silica sol.

[0027] The preparation method of the iron ditch castable of the invention is simple and suitable for wide promotion.

[0028] Beneficial effects of the present invention:

[0029] Compared with the existing Al2O3-SiC-C iron ditch castable for iron ditch, the iron ditch castable provided by the present invention has the following advantages:

[0030] (1) Lighter bulk density, between 1.85-2.1t / m 3 The unit material consumption can be reduced by 20-25%.

[0031] (2) Low thermal expansion coefficient and higher thermal shock resistance.

[0032] (3) Within the molten iron temperature range of about 1450°C, the hot flexural strength is higher (more than twice that of Al2O3-SiC-C iron ditch castable), and it has better resistance to molten iron erosion.

[0033] (4) The sol-gel bonding has better explosion-proof performance. DETAILED DESCRIPTION

[0034] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] Example 1

[0036] The present embodiment provides an iron ditch castable, the raw material composition of which is shown in Table 1, and the preparation method is as follows: fused quartz, silicon carbide, quartz powder, zirconium-containing silicon powder, spherical asphalt, wettable flake graphite, metallic silicon powder, iron scale powder, hydrated calcium silicate, water reducer and explosion-proof fiber are added to a planetary mixer for stirring and mixing, and the mixed bulk material is put into a packaging bag to obtain bagged bulk material.

[0037] The liquid silica sol and the aforementioned bagged bulk materials are sent to the iron ditch site. On-site iron ditch pouring and maintenance: first add the bagged bulk materials into the forced mixer, start the mixer, and add silica sol in proportion (percentage of the bulk material weight) while stirring. After adding silica sol, stir for 2-3 minutes until the material is uniform and has good vibration fluidity, then place the material in the iron ditch to be repaired and vibrate to compact it. Repeat the process of adding, stirring, discharging and vibrating until the iron ditch maintenance is completed.

[0038] The properties of the obtained iron ditch castable are shown in Table 2 below.

[0039] Table 1

[0040]

[0041] Table 2

[0042]

[0043] Example 2

[0044] This embodiment provides an iron ditch castable, the raw material composition of which is shown in Table 3 below, the preparation method is the same as that of Example 1, and the properties of the iron ditch castable are shown in Table 4 below.

[0045] Table 3

[0046]

[0047] Table 4

[0048]

[0049] Example 3

[0050] This embodiment provides an iron ditch castable, the raw material composition of which is shown in Table 5 below, the preparation method is the same as that of Example 1, and the properties of the iron ditch castable are shown in Table 6 below.

[0051] Table 5

[0052]

[0053] Table 6

[0054]

[0055] Example 4

[0056] This embodiment provides an iron ditch castable, the raw material composition of which is shown in Table 7 below, the preparation method is the same as that of Example 1, and the properties of the iron ditch castable are shown in Table 8 below.

[0057] Table 7

[0058]

[0059] Table 8

[0060]

[0061] Comparative Example 1

[0062] This comparative example provides an Al2O3-SiC-C iron ditch castable for existing iron ditch, the composition of which is shown in Table 9 below, and the properties of which are shown in Table 10 below.

[0063] Table 9

[0064]

[0065] Table 10

[0066]

[0067] It can be seen from the experimental results of the above embodiments and comparative examples that, compared with the existing Al2O3-SiC-C iron ditch castable for iron water ditch, the iron ditch castable provided by the present invention has a lighter volume density, a lower thermal expansion coefficient and a higher hot flexural strength.

[0068] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. An iron trough castable, characterized in that: Including fused quartz, silicon carbide, quartz powder, zirconium-containing silicon powder, spherical asphalt, wettable flake graphite, metallic silicon powder, iron scale powder, hydrated calcium silicate, water reducing agent, explosion-proof fiber and silica sol; According to weight proportions, it includes 40-70 parts of fused quartz, 9-18 parts of silicon carbide, 12-26 parts of quartz powder, 2-10 parts of zirconium-containing silicon powder, 1.5-3 parts of spherical asphalt, 1-3 parts of wettable flake graphite, 1.5-3 parts of metallic silicon powder, 0.2-0.5 parts of iron scale powder, 0.05-0.3 parts of hydrated calcium silicate, 0.10-0.25 parts of water reducing agent, 0.05-0.12 parts of explosion-proof fiber and 8.0-10.0 parts of silica sol; The fused quartz comprises 15-25 parts of fused quartz with a particle size of 0-1 mm, 15-25 parts of fused quartz with a particle size of 1-3 mm, and 10-20 parts of fused quartz with a particle size of 3-5 mm; and / or, the content of SiO2 in the fused quartz is ≥99%.

2. The iron ditch castable according to claim 1, characterized in that: The silicon carbide is 98 silicon carbide.

3. The iron ditch castable according to claim 1, characterized in that: The sum of the contents of SiO2 and ZrO2 in the zirconium-containing silicon micropowder is ≥95%, and the particle size is ≤1um.

4. The iron ditch castable according to claim 1, characterized in that: The particle size of the ball pitch is 0-0.5 mm; and / or, the particle size of the wettable flake graphite is 0-0.5 mm; and / or, the particle size of the iron scale powder is 0.04-0.05 mm; and / or, the particle size of the hydrated calcium silicate is 0.07-0.08 mm.

5. The iron ditch castable according to claim 1, characterized in that: The explosion-proof fiber is a hollow explosion-proof fiber.

6. The iron ditch castable according to any one of claims 1 to 5, characterized in that: The iron trough castable satisfies at least one of the following characteristics (1)-(5): (1) Bulk density is 1.85-2.1g / cm 3 ; (2) Thermal expansion coefficient is 1.5-2.5×10 -6 / K; (3) The compressive strength after treatment at 110℃ for 24h is 30-35MPa; the compressive strength after treatment at 1000℃ for 3h is 25-40MPa; the compressive strength after treatment at 1500℃ for 3h is 50-60MPa; (4) The post-sintering line change rate after treatment at 1500℃ for 3h is +(0.1-0.15)%; (5) The hot flexural strength after treatment at 1450℃ for 1h is 5-8MPa.

7. The method for preparing the iron ditch castable according to any one of claims 1 to 6, characterized in that: The steps include: The mixed material is obtained by mixing fused quartz, silicon carbide, quartz powder, zirconium-containing silicon powder, spherical asphalt, wettable flake graphite, metallic silicon powder, iron scale powder, hydrated calcium silicate, water reducing agent and explosion-proof fiber; and the obtained mixed material is stirred evenly with silica sol.

Citation Information

Patent Citations

  • Application of hydrated calcium silicate fiber to prepare aerated concrete blocks

    CN107500642A

  • Refractory castable for blast furnace iron tapping channels

    CN110981514A